Eksplorasi Dinamika Peminjaman Kata dalam Bahasa Arab Modern: Studi Kasus pada Bidang Teknologi dan Sains - Imam Wahyudi; Zainuri; Sulaiman, Muhammad (Al-Kafaah : Journal of Arabic Language and Linguistics Education (ALLE), 2024)
This research explores the dynamics of loanwords in modern Arabic, particularly in the fields of technology and science. Using a descriptive qualitative approach, this study identifies the types of loanwords, the mechanisms of linguistic adaptation, and their impact on Arabic usage. Data were collected through analyzing dictionaries and scientific articles. The findings show that borrowing words from English, such as "computer" and "internet", enriches Arabic vocabulary and facilitates communication in international contexts. The adaptation process involves transliteration, phonological modification, and combining native words with loan words. However, this phenomenon presents a challenge to language scholars who are concerned about the loss of authenticity of Arabic. The study concludes that word borrowing is an integral part of the dynamic and adaptive evolution of the Arabic language, reflecting the ongoing social, economic, and cultural changes in the Arab world.